PELAYANAN ZAKAT HARTA PADA KANTOR BADAN AMIL ZAKAT (BAZ) KOTA PALU PROPINSI SULAWESI TENGAH - Husen, Husen (Katalogis, 2013)
This research aimed to analyze the Propertu Zakat Service at Amil Zakat Agency (BAZ) Palu Central Sulawesi Tengah Province. This research was conducted for 3 (three) months from March to June 2012, it’s location was on the office of Amil Zakat Agency (BAZ) Palu Central Sulawesi Province. Informants in this research were 13 persons consisted of 3 employees of BAZ Palu, 3 persons as obligatory zakat or muzakki in Palu Timur District, 3 persons as obligatory zakat or muzakki in Palu Barat district, 2 persons as zakat recipient or mustahik in Palu Timur distric, 2 persons as zakat recipient or mustahik in Palu Barat distric. Selecting sample used purposive sampling technique where the 13 persons selected as informants. Techniques of data collection in this research used observation, interview, and documentation. Data analysis used descriptive qualitative. This research used the theory of zeithaml who mentioned some indicators in service consisted of reliability, responsiveness, empathy, and tangibles. The results of the research showed the property zakat service at amil zakat agency (BAZ) Palu central Sulawesi province has not been running effectively.it can be seen from the service included socialization, human resources, more facilities showed ineffectiveness of the indicators were chosen as questions of interview guideline.